Summarizing AI Application on Student Learning Efficiency in Understanding Academic Reading Materials - Hutapea, Elizabeth; Hutabalian, Ristama; Hartati, Rita (Indonesian Journal of Education and Development Research, 2025)
Artificial Intelligence (AI) has fundamentally transformed educational methodologies, particularly in enhancing students' learning efficiency and comprehension of academic reading materials. This research investigates the role of AI applications in supporting students' understanding of complex academic texts. Utilizing a mixed-method approach with 30 university student respondents, the study explores how AI tools impact reading comprehension, study efficiency, and academic skill development. The findings reveal that 70% of students consistently use AI applications for academic reading, with 83.3% finding AI-generated summaries understandable. Approximately 60% of respondents reported increased study time efficiency, and 70% experienced improved confidence in understanding academic materials. While the study highlights the potential of AI in educational support, it emphasizes the need for critical engagement and careful integration of these technologies into academic learning processes.